Co-expression of Foxp3 and Helios facilitates the identification of human T regulatory cells in health and disease - Morina, Lyra; Jones, Madalyn E.; Oguz, Cihan; Kaplan, Mariana J.; Gangaplara, Arunakumar; Fitzhugh, Courtney D.; Kanakry, Christopher G.; Shevach, Ethan M.; Buszko, Maja (Frontiers in Immunology, 2023)
Foxp3 is regarded as the major transcription factor for T regulatory (Treg) cells and expression of Foxp3 is used to identify and quantitate Treg cells in mouse models. However, several studies have demonstrated that human CD4+ T conventional (Tconv) cells activated in vitro by T cell receptor (TCR) stimulation can express Foxp3. This observation has raised doubt as to the suitability of Foxp3 as a Treg marker in man. Helios, a member of the Ikaros gene family, has been shown to be expressed by 80-90% of human Foxp3+ Treg cells and can potentially serve as a marker of human Treg. Here, we confirm that Foxp3 expression is readily upregulated by Tconv upon TCR stimulation in vitro, while Helios expression is not altered. More importantly, we show that Foxp3 expression is not elevated by stimulation of hTconv in a humanized mouse model of graft versus host disease (GVHD) and in patients with a wide variety of acute and chronic inflammatory diseases including sickle cell disease, acute and chronic GVHD, systemic lupus erythematosus, as well as critical COVID-19. In all patients studied, an excellent correlation was observed between the percentage of CD4+ T cells expressing Foxp3 and the percentage expressing Helios. Taken together, these studies demonstrate that Foxp3 is not induced upon Tconv cell activation in vivo and that Foxp3 expression alone can be used to quantitate Treg cells in humans. Nevertheless, the combined use of Foxp3 and Helios expression provides a more reliable approach for the characterization of Treg in humans.